(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2021)
Identification of natural springs, emerging in the gorges of mountain rivers, and those long-term qualitative and quantitative observations allow to substantiate the prospects of their use for water supply to settlements. Undoubtedly, long-term hydrogeological studies are very productive, but at the same time, very expendable. The paper proposes to correlate the data of short-term observations with the calculated balance of water resources, as well as to assess the probability of the minimum discharge by the method of statistical analysis. The studies were carried out according to the data of springs discharging on the northern slopes of the mountain of Aragats in the Mantash River basin.